2008
DOI: 10.1021/la703064m
|View full text |Cite
|
Sign up to set email alerts
|

Electroless Gold Island Thin Films:  Photoluminescence and Thermal Transformation to Nanoparticle Ensembles

Abstract: Electroless gold island thin films are formed by galvanic replacement of silver reduced onto a tin-sensitized silica surface. A novel approach to create nanoparticle ensembles with tunable particle dimensions, densities, and distributions by thermal transformation of these electroless gold island thin films is presented. Deposition time is adjusted to produce monomodal ensembles of nanoparticles from 9.5 +/- 4.0 to 266 +/- 22 nm at densities from 2.6 x 1011 to 4.3 x 108 particles cm-2. Scanning electron micros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
91
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(94 citation statements)
references
References 83 publications
3
91
0
Order By: Relevance
“…Acid etching followed by substrate hydroxylation supports chemisorption of tin (II), improving adherence to the substrate [13]. While the extent of tin (II) interlocking on soda lime glass was not examined directly in this report, previous work showed that nitric acid etching before tin sensitization and subsequent reduction of silver nitrate (AgNO 3 ) followed by galvanic replacement with Au improved Au adhesion to glass substrates [14,39]. Also, Minjer et al used nitric acid treatment of soda lime glass following immersion in sulfuric and chromic acids to remove sodium ions and other impurities [25].…”
Section: Substrate Pre-treatmentmentioning
confidence: 89%
See 2 more Smart Citations
“…Acid etching followed by substrate hydroxylation supports chemisorption of tin (II), improving adherence to the substrate [13]. While the extent of tin (II) interlocking on soda lime glass was not examined directly in this report, previous work showed that nitric acid etching before tin sensitization and subsequent reduction of silver nitrate (AgNO 3 ) followed by galvanic replacement with Au improved Au adhesion to glass substrates [14,39]. Also, Minjer et al used nitric acid treatment of soda lime glass following immersion in sulfuric and chromic acids to remove sodium ions and other impurities [25].…”
Section: Substrate Pre-treatmentmentioning
confidence: 89%
“…TFA concentrations of 30, 68, and 90 mM were tested at sensitization concentration and time of 26 mM and 30 s, respectively. TFA was used instead of HCl during sensitization, due to reports indicating tin (II)-TFA sensitization was effective for subsequent EL plating of uniform gold films with features closely resembling sputtered gold films [7,13,29,30,34,39]. However, tin sensitization in the presence of TFA may reduce tin (II) on substrates, and produce larger grain size and higher pK a (0.23) than HCl (−7.0) [13].…”
Section: Aqueous Immersionmentioning
confidence: 96%
See 1 more Smart Citation
“…19 a͒ Electronic mail: dkroper@uark.edu Electroless plating of gold uses sequential metal depositions of tin ͑Sn 2+ ͒, silver ͑Ag + ͒, and gold ͑Au͒ to give strong adhesion of Au particles to the substrate. 10,20 Upon thermal annealing, EL plated Au thin films transform to thermally stable, spherical NP assemblies with adjustable size and density relative to evaporated Au films that detach from the substrate under intensive laser irradiation using Nd:YAG ͑yttrium aluminum garnet͒. 21,22 Our novel bottom-up approach pairs EBL with EL Au plating to create thermally stable regular arrays of Au nanospheres on a silica substrate.…”
Section: Introductionmentioning
confidence: 99%
“…3,[5][6][7][8][9] Widespread use of EBL allows precise preparation of metal arrays via metal thin film evaporation or sputtering, but top-down metal deposition limits particle shapes to cylindrical structures and precludes thermal shape transformation due to weak bonding between the metal film and substrates. We recently reported thermal transformation of Au island thin films created by electroless ͑EL͒ Au plating to random assemblies of spherical Au NPs on planar silica substrates 10 and on the inner walls of rectangular borosilicate glass capillaries. 11 Here we present a novel "bottom-up" approach to creating stable, regular arrays of Au nanospheres on a silica substrate via thermal coalescence of EL plated Au islands patterned using EBL that allows particle size, spacing, and shape to be controlled.…”
Section: Introductionmentioning
confidence: 99%